Total pancreatectomy for the treatment of pancreatic neoplasms. Issue 11 (22nd April 2014) - Nikfarjam, Mehrdad; Low, Nicholas; Weinberg, Laurence; Chia, Ping Han; He, Hong; Christophi, Christopher
Abstract Background Total pancreatectomy (TP) is an operation that has long been associated with high morbidity and mortality, and rarely advocated for treatment of pancreatic tumours. Because of the improvements in diabetes management, there has been renewed interest in TP for treatment of pancreatic neoplasm, with a need to reassess outcomes. Methods Fifteen patients (9%) underwent TP in a single Australian high‐volume tertiary institution between August 2005 and January 2012. Pancreaticoduodenectomy (PD) was performed in 150 patients during the same time period. Indications and peri‐operative outcomes of patients were compared. Results TP was performed for treatment of malignancy in 13 (87%) cases, for tumours involving the pancreatic neck. Complete tumour clearance achieved. Portal vein resections were more frequently required than in the PD group (5 (33%) versus 9 (6%); P = 0.004), as were blood transfusions (11 (73%) versus 28 (19%); P < 0.001), and median operative times were longer (10.5 versus 7.0 h; P < 0.001). Overall, complications were significantly greater in the TP group compared with the PD group (13 (87%) versus 86 (57%); P = 0.029), but the difference was mainly as a result of high grade I complications, in particular symptomatic hypoglycaemia (4 (27%) versus 0 (0%): P < 0.001) that could be easily managed. The overall lengths of stay and readmission rates were similar between groups. Conclusion TP should be considered in selective cases for treatment of pancreatic neoplasm if it allows complete clearance. The procedure does not appear to be associated with significant increases in serious complications compared with PD.